Penggunaan Elektro Pneumatik dalam Efisiensi Waktu Pemotongan Kentang Berbasis Programmable Logic Controller - Agustina, Dwi; Yurika, Yurika (Universitas Pahlawan Tuanku Tambusai, 2024)
Potato cutting machines have become tools used in the modern manufacturing industry in the production of various processed potato products. Technological developments also continue in this field, thereby increasing production efficiency and quality. One important thing is its application because it uses an electro-pneumatic system on a potato cutting machine. This system integrates traditional pneumatic technology with advanced electronic control and produces a powerful combination that optimizes the potato cutting process. In this study, we also present a comprehensive review regarding the use of electro-pneumatic systems in potato cutting machines. The application of this electro-pneumatic system to potato cutting machines provides great potential to increase production efficiency and quality. We can see that the cutting process using a pneumatic cylinder based on a programmable logic controller is more efficient in terms of time than manual cutting. Where it only takes 2 seconds at 8 bar pressure.